2008
DOI: 10.1007/s12204-008-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of continuous maglev guideway considering the magnetic levitation system

Abstract: The dynamic interaction between moving vehicles and two-span continuous guideway was discussed. With the consideration of the magnetic levitation system, the maglev vehicle/guideway dynamic interaction model was developed. Numerical simulation was performed to understand dynamic characteristics of the guideway used in practice. The results show that vehicle speed, span length and primary frequency of the guideway have an important influence on the dynamic responses of the guideway and there is no distinct tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…In order to verify the superiority of this algorithm,combined with the research proposed by Teng et al [12] , the COST231-Hata path loss model is selected, which is often applied to signal prediction in urban areas.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…In order to verify the superiority of this algorithm,combined with the research proposed by Teng et al [12] , the COST231-Hata path loss model is selected, which is often applied to signal prediction in urban areas.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…The mode shape of the two-span continuous beam can be divided into two groups, which are symmetrical and asymmetrical, respectively [12]. The circular frequency can be identified as…”
Section: Natural Frequency and Mode Shape Functionsmentioning
confidence: 99%
“…The model of guideway has been treated as simply supported Euler-Bernoulli beam by several authors as found in the articles published by Cai et al [2], Ren et al [3], Wang et al [4], Zhao and Zhai [5] and Zheng et al [6]. Teng et al [7] investigated the response of two-span continuous guideway for high-speed magnetic levitation system using moving distributed load without considering the effect of MAGLEV suspension systems.…”
Section: Introductionmentioning
confidence: 99%